EFEKTIVITAS MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA WORDWALL TERHADAP HASIL BELAJAR SISWA KELAS IV PADA MATA PELAJARAN IPAS - Rahman, Putri Aisyah; Baalwi, Muhammad Assegaf; Lestari, Wahyu Maulida (Jurnal Muassis Pendidikan Dasar, 2025)
Games Tournament) learning model supported by Wordwall media on the learning outcomes of Grade IV students in the IPAS (Science) subject on the topic of energy. This study is a pre-experimental type with a One Group Pretest-Posttest design, where the researcher compares the pretest results (before treatment) with the posttest results (after treatment). Data were collected through tests using test sheets as the main instrument. Data analysis includes validity testing, reliability testing, normality testing, and hypothesis testing using the paired sample t-test, analyzed using IBM SPSS version 22 software. Based on the normality test, it was found that the data is normally distributed; therefore, the hypothesis test used is the paired sample t-test. Based on the paired sample t-test, a sig. (2-tailed) value of 0.000 < 0.05 was obtained, meaning that Ho is rejected and Ha is accepted. Therefore, it can be concluded that the TGT learning model supported by Wordwall media is effective in improving the learning outcomes of Grade IV students in the IPAS subject on energy at SDN Bligo Candi Sidoarjo